Happy-Victimizing in Adolescence and Adulthood: Empirical Findings and Further Perspectives - Heinrichs, Karin; Gutzwiller-Helfenfinger, Eveline; Latzko, Brigitte; Minnameier, Gerhard; Döring, Bettina (Frontline Learning Research, 2020)
Research on the Happy Victimizer Phenomenon has mainly focused on preschool and schoolchildren, with a few studies also including adolescents and young adults. The main finding is that young children, despite knowing that harming somone is wrong, ascribe positive feelings to perpetrators and offer hednonistic justifications, interpreted as a lack of moral motivation. Only at age 9 or 10 do almost all children ascribe negative feelings to perpetrators. According to the developmental transition hypothesis, the phenomenon should disappear in late childhood. However, reasoning patterns resembling that of the Happy Victimizer have been found in studies with adolescents and young adults, challenging that hypothesis. We present findings from four studies involving adolescents and young adults to give an overview of the patterns found and the measurement approaches used. Finally, we critically discuss the limitations of those studies and raise some core theoretical and methodological issues that remain to be resolved, some of them being addressed in the remaining papers of this special issue. The four studies and the paper are innovative in that (a) situational factors are included in the measurement of the moral reasoning patterns; (b) new reasoning patterns are identified in the context of an extended measurement approach; and (c) the moral reasoning patterns are investigated in their own right and not used as potential explanatory variables for behaviour, as has been the main focus of research on the Happy Victimizer Phenomenon.